Measuring the Economically Active in Population Censuses - United Nations Department of Economic; Social Affairs (United Nations, 2013)
The Handbook provides guidance on the measurement of economic characteristics in population censuses, based on relevant experiences of countries, with a particular focus on the questions used and the requirements for processing of responses. The Handbook is intended to provide census planners with a variety of approaches to assess the questions and methods of collecting economic characteristics used in their national census, as they evaluate the performance in the past decade and plan for the 2010 round of censuses (2005-2014). Users of census results may also find the present text useful when evaluating the quality of census results.